Effect of Lissachatina fulica chitosan on the antioxidant and lipid profile of hypercholesterolemic male Wistar rats - Umarudin; Sri Widyarti; Warsito; Sri Rahayu (GarVal Editorial Ltda., 2022)
Context: The increase in reactive oxygen species production in hypercholesterolemia can degrade polyunsaturated fatty acids and form malondialdehyde (MDA). There is a need for a natural alternative treatment, such as Lissachatina fulica chitosan. Aims: To analyze the potential of Lissachatina fulica chitosan in increasing the superoxide dismutase (SOD) level, reducing lipid profile, and MDA level of male Wistar rats with hypercholesterolemia model. Methods: The male Wistar rats were divided into six groups (n = 4): P0 (normal control); P1-P5 fed a high-fat diet for four weeks. P1 were treated with fed with a high-fat diet; P2 were treated with ezetimibe of 0.18 mg/200 g BW; P3, P4, and P5 Groups; fed with a high-fat diet and Lissachatina fulica chitosan of 100 mg, 200 mg, and 300 mg/200g BW, respectively. The lipid profile was conducted in rat blood samples by using the CHOP-PAP method, the MDA analysis using the TBARS test, and SOD assay analysis using a kit. Results: The results reveal that the treatment Lissachatina fulica chitosan (300 mg/200 g BW) was significantly effective (p<0.05) to decrease in total cholesterol level (96.7 ± 1.9 mg/dL), triglyceride (75.6 ± 1.6 mg/dL), LDL (29.8 ± 2.5 mg/dL), and MDA (1.2 ± 0.1 nmol/mL) as well as a significant increase (p<0.05) in HDL level (75.0 ± 1.7 mg/dL) and SOD (74.6 ± 2.1 unit/mL). Conclusions: Lissachatina fulica chitosan can reduce total cholesterol, triglyceride, LDL, and MDA, and increase HDL and SOD levels.